Valorant as a Digital Game-Based Platform for EFL Speaking Practice: A Mix-Methods Study of Learner Perceptions - Ardanna, Satrio Febrian; Hapsari, Christianti Tri (JELITA, 2026)
This study explores EFL learners’ perceptions of using Valorant as a medium for developing speaking skills in an EFL context. While digital game-based learning has been widely studied, the use of commercial multiplayer games for spontaneous English speaking practice remains underexplored. This study employs a mixed-methods design involving 20 questionnaire respondents and five participants in semi-structured interviews. Data were collected through close-ended questionnaires and follow-up interviews. The questionnaire data were analyzed using descriptive statistics (frequencies and percentages), while the interview data were analyzed using thematic analysis within an interactive model of data analysis, including data reduction, data display, and conclusion drawing. The findings reveal that voice chat in Valorant is perceived as a useful and engaging tool for practicing English speaking, particularly in improving fluency, confidence, and real-time communication. It is also considered relatively easy to use, although challenges related to communication clarity and limited vocabulary persist. Additionally, playing Valorant enhances learners’ motivation to use English through both intrinsic and extrinsic factors. However, learning practices tend to be informal, relying on spontaneous strategies such as listening, imitation, and repetition rather than structured planning. In conclusion, Valorant demonstrates strong potential as a complementary tool for supporting EFL speaking development, particularly when integrated into Computer-Assisted Language Learning (CALL) or informal learning frameworks, although its effectiveness depends on individual differences.